A signal quality assessment method for fetal QRS complexes detection - Wei Zhong; Li Mao; Wei Du (Mathematical Biosciences and Engineering, 2023)
Objective: Non-invasive fetal ECG (NI-FECG) provides a non-invasive method to monitor the health of the fetus. However, the NI-FECG is easily interfered by noise, which makes the signal quality decline, leading to the fetal heart rate (FHR) monitoring becoming a challenging task.